Patients' experience of a regional allergy service - Ray Jones; Anita O'Connor; Edward Kaminski (SAGE Publishing, 2013)
Background. The principle reason for referral to specialist allergy clinics is to establish diagnoses and provide treatment plans to help patients manage their allergy. If patients do not accept, understand, or remember diagnoses or treatment, clinic visits may have been a waste of time. Few specialist allergy clinics follow up patients after diagnosis. Design and Methods. This was a postal survey to assess patients' i) perception of usefulness of specialist allergy clinic visits, ii) under- standing of their allergy, iii) confidence in managing it, and iv) response to joining a regional online forum. Data for patients with confirmed allergy who attended the Peninsula Allergy Service (PAS) from 1998-2009 were extracted from consultant letters to general practitioners. Postal questionnaires were sent to 933 patients; 39% (336) responded. Results. Two-thirds (63%) thought their clinic visit useful and resulted in them being more in control of their allergy; 9% thought it useful but they still had problems, 26% thought it had not been much use. One in six (16%, 55) respondents had major differences in their view of their allergy compared to that recorded by PAS. Over half (56%) had had further symptoms since their clinic visit and 120 patients, who were not confident in coping with their allergy, listed aspects of their lives that gave concern. Conclusions. Specialist clinics need routine feedback from patients if they are to monitor their effectiveness and some better form of follow up for patients is needed to reinforce education and support patients. Public education is important.